Anti-acute inflammatory effect of hibiscus rosa-sinensis l. and hibiscus rosa-sinensis var. alba flower and leaf ethanol extracts and its mechanism of action in rats - Raduan, Siti Zaleha (2013)
Hibiscus rosa-sinesis L. is a plant having medicinal properties especially its flower and leaf but not much on its variant; alba. The study was carried out to determine and compare the anti-acute inflammatory activities and its mechanism of action of ethanol extract of flower and leaf of Hibiscus rosa-sinensis var alba (white) and Hibiscus rosa-sinensis L. (red) in rats. Phytochemical screening was performed with 95% ethanolic crude extracts. Flavanoids, saponins and steroids presence in all extracts. Acute dose response was determined using Fixed Dose Procedure with fixed level of dose. Any signs of toxicity were observed within 14 days. Supplementation of 500 mg/kg of all extracts caused toxicity. The blood samples were collected and liver and kidney were isolated at day 15. No significant changes (p>0.05) in liver enzyme levels and histologically no presence of lesions at the organs as response up to 500 mg/kg. For anti-inflammatory properties, edema and polymorphonuclear leukocyte (PNL) infiltration induced by carrageenan and licking time induced by formalin were studied. 0.1ml of carrageenan was injected subplantarly 30 min before administration of each extracts (5, 50 or 100 mg/kg). Supplementation of 50 and 100 mg/kg of flower and leaf of Hibiscus rosa-sinensis L. caused significant inhibition (p<0.05) of edema. Flower and leaf of Hibiscus rosa-sinensis var alba significantly inhibited (p<0.05) edema in all range of testing dose. It varies significantly (p<0.05) with variant, plant parts and doses. The animals were killed after 6 hrs and PNLs in paw tissues were counted. Supplementation of all extracts at various concentration caused significant reduction (p<0.05) on PNL infiltration. It varies significantly (p<0.05) with dose but no significant (p>0.05) with variant and plant parts. 50μl of formalin was injected subplantarly 30 min before administration of 100 mg/kg of each extracts. Supplementation of all extracts showed significant reduction (p<0.05) on the duration of licking response. It varies significantly (p<0.05) with variant but no significant (p>0.05) with plant parts and phase. For anti-acute inflammatory mechanism, edema and PNL infiltration induced by bradykinin (BK) and histamine were studied. 0.1ml of BK was injected subplantarly 15 min before administration of 100 mg/kg of each extracts. Supplementation of all extracts showed significant inhibition (p<0.05) of edema. It varies significantly (p<0.05) with variant but no significant (p>0.05) with plant parts. The animals were killed after 6 hrs and PNLs in paw tissues were counted. Supplementation of all extracts showed significant reduction (p<0.05) on PNL infiltration. It varies significantly (p<0.05) with variant and plant parts. 0.1ml of histamine was injected subplantarly immediately before administration of 100 mg/kg of each extracts. Supplementation of all extracts showed significant inhibition (p<0.05) of edema. It varies significantly (p<0.05) with variant but no significant (p>0.05) with plant parts. The animals were killed after 2 hrs and PNLs in paw tissue were counted. Supplementation of all extracts showed significant reduction (p<0.05) on PNL infiltration. It varies significantly (p<0.05) with variant but no significant (p<0.05) with plant parts. In conclusion, the study showed flower and leaf of Hibiscus rosa-sinensis var alba and Hibiscus rosa sinensis L. produced anti-acute inflammatory activity. It may involve the inhibition of cyclooxygenase, bradykinin, histamine, and reduce polymorphonuclear infiltration.